P-025 Outcome study of pipeline embolisation device with shield technology in unruptured aneurysms. (22nd July 2019) - Kandasamy, N; Booth, T; Hart, J; Atasoy, D; Shih-hung, Y
Abstract : Background: Pipeline Flex Embolization Device with Shield Technology (Pipeline Shield) has recently been introduced as the third generation of Pipeline flow-diverter devices (FDDs) with a new stent surface modification giving reduced thrombogenicity. Objective: We aimed to evaluate clinical (safety) and radiographic (efficacy) outcomes of the Pipeline Shield. Methods: The 30 day and 1-year mortality and morbidity rates, and the 6 and 18 month radiographic aneurysm occlusion outcomes for procedures performed between March 2016 and January 2018, were reviewed. 3D-TOF-MRA was used for follow up. Results: A total of 44 attempted Pipeline Shield procedures were performed for 41 patients with 44 target aneurysms (total 52 aneurysms treated). 88.5% were inserted in the anterior circulation and 11.5% the posterior circulation. 49/52 (94.2%) aneurysms were saccular, 1/52 (1.9%) was fusiform. One (1.9%) aneurysm was an iatrogenic pseudoaneurysm and one (1.9%) was a dissecting aneurysm. 71% (35/49) of the saccular aneurysms were wide-necked (neck >4 mm), 34.6% (18/52) were large (≥ 10 mm) and 3.8% (2/52) were giant (≥ 25 mm). The mean aneurysm sac maximal diameter was 9.2 mm, and mean neck width was 5.1 mm. The cumulative mortality and morbidity rates were 2.3% and 9.2% at 1 year, respectively. The adequate occlusion rate was 78.8% at 6 months and 90.3% at 18 months. Conclusions: In this pragmatic and independent study, the occlusion rates and safety outcomes were similar to those seen in previously published studies with FDDs and earlier generation PEDs. Disclosures: N. Kandasamy: 6; C; contribution towards institutional study budget. T. Booth: 6; C; institutional study budget support. J. Hart: 6; C; Institutional study budget support. D. Atasoy: None. Y. Shih-hung: None.